Existential semiotics - Tarasti, Eero (Advances in semiotics., 2000)
"Existential semiotics posits an a priori state of signs; it studies the ways in which signs are fixated into objective entities. Tarasti's work is hermeneutic and phenomenological, with its sources in Husserl, Schutz, Merleau-Ponty, Hegel, Schelling, Kierkegaard, Jaspers, and Heidegger. As a member of the Paris School of Semiotics (and following the lead of A.J. Greimas, in particular). Tarasti is seeking less-categorical, less-Cartesian approaches. He sees semiotics in transition, shift, rupture, and flux, something which is "becoming" rather than "being."